Cover Image. (7th October 2020) - Yamamoto, Yosuke; Matsusaka, Keisuke; Fukuyo, Masaki; Rahmutulla, Bahityar; Matsue, Hiroyuki; Kaneda, Atsushi
Abstract : The cover image is based on the Original Research Higher methylation subtype of malignant melanoma and its correlation with thicker progression and worse prognosis by Yosuke Yamamoto et al., https://doi.org/10.1002/cam4.3127